Money illusion under test - Stefan Boes; Markus Lipp; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2005)
Much progress has been made in recent years in developing and applying a direct measure of utility using survey questions on satisfaction with income and with life in general. In this paper we apply this new type of measurement to the study of money illusion. Using data from the German Socio-Economic Panel for the years 1993 to 2003, we cannot reject the hypothesis of no money illusion.
Keywords: I31; D12; 330; cost-of-living; subjective well-being; fixed effect; Geldillusion; Verbraucherpreisindex; Lebensqualität; Panel; Deutschland